Legal Protection for Children Born Out of Wedlock: An Islamic Justice Perspective - Umi Enggarsasi; Nur Khalimatus Sa'diyah; Muhammad Dhany Reformasi (APPTHI, 2024)
The presence of a child born outside of marriage raises various issues both within families and society, particularly regarding the rights and obligations of the child. A child born out of wedlock may not solely result from an illicit relationship; it can also occur when a marriage is conducted only according to customary law without being officially registered. According to Article 80 of the Civil Code, prior to the Marriage Law, marriage must be performed in front of a Civil Registry official. Article 81 stipulates that religious ceremonies must occur after the civil registration. This research aims to analyze the implementation of birth registration regulations for children born out of wedlock based on Islamic justice, identify weaknesses in issuing birth certificates without a marriage certificate, and reconstruct these regulations in alignment with Islamic values. The research employs a constructivist paradigm, using a sociological-legal approach and various data collection methods. Findings indicate that the implementation of birth registration for children born out of wedlock lacks fairness, necessitating protection to ensure equal treatment with other children. Current regulations are insufficiently clear regarding children born out of wedlock, highlighting a need for better synergy among law enforcement. The reconstruction of these regulations is outlined in Law No. 23 of 2006 and the more recent Law No. 24 of 2013 regarding population administration.